Pelatihan Pemupukan Anggrek untuk Mahasiswa Biologi Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Tanjungpura Pontianak Kalimantan Barat - Dwi Gusmalawati; Zulfa Zakiah; Riza Linda; Surya Abi Alfariz; Niluh Kharina Asoka Putri (I-Com: Indonesian Community Journal, 2024)
Orchids are highly economic plants due to the beauty of their flowers. Orchid cultivation is important in order to fulfil the increasing demand for orchids in the market. Fertilisation is an important stage in orchid cultivation in order to get fast flowering orchids. The purpose of this activity is to increase students' understanding and ability in fertilising orchids. Partners in this activity are Biology students of the Faculty of Mathematics and Natural Sciences, Tanjungpura University. This activity has several stages, namely planning (determination of time, preparation of tools and materials), implementation (provision of material, demonstration, fertilisation practice) and evaluation (questionnaire). The knowledge and ability of Biology students in caring for orchids has increased. Participants were very satisfied reaching 92.86% after participating in this training. Participants also experienced an increase in the material and practice of orchid fertilisation by 85.71%. This activity was able to increase understanding and ability about orchid fertilisation. The understanding and skills in orchid fertilisation obtained are expected to be able to be practised at home in caring for orchids so that they flower quickly.